Kiat-Kiat Dan Strategi Memahami Konflik - Achmad Asfi Burhanudin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
Conflict is something that cannot be avoided by anyone. Conflict is closely embedded in the fabric of life. Both individuals, groups and organizations who always struggle to win conflicts. Conflict has occurred since human existence in this world, along with the more advanced human mindset, the existence of conflict is growing and complex day by day. Thus it can be concluded that there is no day without conflict. Therefore, it is required to pay attention and manage conflicts carefully and seriously. To be successful in managing conflict, we need to understand conflict well. Understanding means understanding or knowing something in depth. Understanding is more than just knowing, understanding requires detailed mastery of a thing, its ins and outs, even its origin. Efforts and approaches to conflict resolution include: Conflict prevention seeks to prevent the outbreak of violent conflict, Conflict settlement seeks to end violent behavior by reaching peace agreements, Conflict management aims to limit and avoid violence that may occur in the future by supporting positive behavior change on the parties involved, Conflict resolution (conflict resolution) addresses various causes of conflict and tries to build new and lasting relationships between groups that are mutually hostile, Conflict transformation ( conflict transformation) discusses broader political and social sources of conflict and tries to transform the negative energy of war into positive social and political change. The forms of conflict resolution commonly used are conciliation, mediation, arbitration, arbitration